Innovation Potential and Tourism Development in the EU: The Impact of Digitalisation and Research Investment on Tourism Performance - Kubickova, Viera; Harcsova, Henrieta; Bruskova, Barbora (Transformations In Business & Economics, 2025)
This paper examines the relationship between the innovation potential of the economy and tourism development in European Union countries, using data from indices such as the European Innovation Scoreboard (EIS), the Tourism and Travel Development Index (TTDI), the Digital Economy and Society Index (DESI), and statistics from UNWTO and Eurostat. Spearman’s correlation coefficient measures the strength and direction of the relationships, revealing moderate to strong correlations between innovation potential and tourism performance. The results show that investment in research and development (GERD) and digitalisation (DESI) significantly enhance the development of the innovation potential of tourism. Countries with higher digitalisation and innovation investments outperform in tourism, while the use of European funds (ERDF/CF) shows weaker or negative correlations. The findings underline the importance of supporting innovation strategies that focus on digital technologies, research and sustainable tourism development, while collaboration between the public and private sectors can be key to maximising innovation opportunities.